Exploring role of environmental proactivity in financial performance of manufacturing enterprises: a structural modelling approach. (1st December 2015) - Sen, Parag; Roy, Mousumi; Pal, Parimal
Abstract: In the backdrop of overwhelming concern for greenhouse gas emission, global warming and overall environmental degradation, many manufacturing enterprises are now integrating their manufacturing philosophy with proactive environmental management approach. It is uppermost in the minds of many whether such environmental proactive approach will also help to improve financial performance of the manufacturing enterprises. This study explores this pertinent issue in the context of manufacturing enterprises of two democratic countries from the east and the west, India and UK respectively. Data collected through a questionnaire validated by invited experts distributed among manufacturing enterprises of India and UK were used to construct the structural model for testing the relationship between environmental proactivity and financial performance. The fitness and robustness of the structural model can be considered adequate. The results indicate positive correlation of environmental proactivity with financial performance, manufacturing based operational performance and non-manufacturing based operational performance. Model equations derived from structural analysis, however, reveal much stronger positive correlation of financial performance with manufacturing based operational practices than with the non-manufacturing based operational practices. The novelty of this research work lies in its managerial implications. It is suggested from the research that the manufacturing enterprises of India and UK should focus more on the manufacturing based operational practices than non-manufacturing based operational practices in order to improve environmental and as well as financial performance. Highlights: The relationships of environmental proactivity with financial performance, MOP and NOP are examined. Manufacturing organizations of India and UK are considered. Environmental proactivity helps to improve financial performance. Financial performance is predominantly influenced by MOP compared to NOP. Life cycle assessment and environmental risk management may highly influence each other.